2004
DOI: 10.1007/s00464-003-8145-6
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic cholecystectomy for biliary dyskinesia

Abstract: Laparoscopic cholecystectomy alleviated symptoms in 94% of patients with a gallbladder EF <14% after CCK injection. The diagnostic significance of a preoperative CCK cholescintigram (EF 14-35%) needs further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…[9][10][11] The patients with an EF less than 14% or with pain after cholecystokinin infusion had a 94% success rate after cholecystectomy. In comparison, the patients with a 14% to 34% EF achieved only a 65% success rate after LC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] The patients with an EF less than 14% or with pain after cholecystokinin infusion had a 94% success rate after cholecystectomy. In comparison, the patients with a 14% to 34% EF achieved only a 65% success rate after LC.…”
Section: Discussionmentioning
confidence: 99%
“…Pain is often exacerbated with food, associated frequently with nausea and vomiting. [10][11][12] If all other diagnostic work-ups are negative, and the patient still has disturbing right upper quadrant pain, quantitative cholescintigraphy may be diagnostic for gallbladder dysfunction. [12][13][14] Our goal was to find out the prevalence of gallbladder dysfunction in the adult population with chronic biliary-type upper abdominal pain.…”
mentioning
confidence: 99%
“…It is clinically accepted that when a GB ejection fraction (percentage of the volume displaced during emptying) is less than 35% [7] or 40% [8], then the GB motor function is considered to be impaired; otherwise, it is considered normal. It has been found that the GB pain of some patients has been alleviated after their GBs are removed [7,8]. However, conflicting reports also exist [3,5,9].…”
Section: Introductionmentioning
confidence: 99%
“…As an indication for cholecystectomy (CCY), GBD is approximately threefold more common in women and has been noted to increase steeply over the past several decades [9,10,11]. Because, as is widely recognized, the symptoms of SOD and GBD do overlap [2], and both entities should be considered in evaluating a patient thought to have either one or the other disorder, making a distinction between the two can be challenging for the clinician.…”
Section: Introductionmentioning
confidence: 99%